2019
DOI: 10.1088/1755-1315/268/1/012076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of TiO2 and MWCNT Nanofluids-based Photovoltaic-Thermal (PV/T) System

Abstract: Nanofluids as a new generation of cooling fluid has been found in recent years to improve the heat-transfer coefficient and enhance the system performance. This study presents investigation conducted on the performances of TiO2 and MWCNT nanofluids-based PVT systems. The preparation of nanofluids using two step method and dispersing of surfactant for a stable nanofluid. The experimental investigation with the effect of different concentration, mass flow rate (0.012 kg/s to 0.0255 kg/s) and solar radiation (500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Asadi et al [52], Almanassra et al [53], and Chen et al [54] all applied the two-step process in synthesizing MWCNTs-water nanofluids. This method has also been used for metal oxide nanofluids like CuO water nanofluid [55], Fe 2 O 3 water nanofluid [56], SiO 2 glycerol-water nanofluid [57] and have also been used in the synthesis of hybrid nanofluids [58][59][60].…”
Section: Nanofluid Synthesis Techniques and Stabilitymentioning
confidence: 99%
“…Asadi et al [52], Almanassra et al [53], and Chen et al [54] all applied the two-step process in synthesizing MWCNTs-water nanofluids. This method has also been used for metal oxide nanofluids like CuO water nanofluid [55], Fe 2 O 3 water nanofluid [56], SiO 2 glycerol-water nanofluid [57] and have also been used in the synthesis of hybrid nanofluids [58][59][60].…”
Section: Nanofluid Synthesis Techniques and Stabilitymentioning
confidence: 99%
“…Rukman et al 169 verified in practice the utility of nano-TiO 2 and MWCNT as heat transfer fluids. Results showed that when using 1% of nano-TiO 2 the degree of PV unit decreased to 1.80 C. Reference 170 provided by a review of practical and theoretical studies that examined the impact of the use of nanofluids on the performance of PV/Ts.…”
Section: Nanofluids and Nanoparticles In Pv/tmentioning
confidence: 99%
“…Rukman et al 169 verified in practice the utility of nano‐TiO 2 and MWCNT as heat transfer fluids. Results showed that when using 1% of nano‐TiO 2 the degree of PV unit decreased to 1.80°C.…”
Section: Application Of Fluids In Pv/tmentioning
confidence: 99%
“…At 900 W/m 2 irradiance, electrical efficiency increased by 6.95% and 7.32% at 0.5 wt.% and 1.0 wt.% titania nanoparticle concentration, respectively, as compared with the uncooled PV panel. In another study, Rukman et al [13] analyzed the performance of the PV/T system using MWCNT and TiO 2À based nanofluids. They concluded that the flow rate increment causes the module surface temperature to decrease, whereas the irradiation increase causes the temperature to increase, and the efficiency gets dropped.…”
Section: Thermal Management Of Photovoltaic Modulesmentioning
confidence: 99%